GE_GERICHTE P/1765/2014 vom 5. Oktober 2015 - GE Cour de justice (2015)
TENTATIVE(DROIT PÉNAL); DOL ÉVENTUEL; IN DUBIO PRO REO; PRÉSOMPTION D'INNOCENCE; MEURTRE; CHANTAGE; VOL(DROIT PÉNAL); CONCOURS D'INFRACTIONS; CONTRAVENTION | CP.111; CP.156; CP.139; CP.172ter; CP.12; CP.22; CP.47; CP.49; CP.106; CP.48.1.c